2003
DOI: 10.1097/01.brs.0000058724.95657.55
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Anatomy of the Lateral Mass of the Atlas

Abstract: Very little information on the lateral mass of the atlas can be found. This study gives some parameters of the lateral mass of the atlas. On the basis of this study, it may be concluded that there is enough space for lateral mass screws in posterior up-cervical internal fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 17 publications
1
20
0
9
Order By: Relevance
“…The height of the lateral mass was found to be 19.60 ± 2.24 mm on the left and 19.56 ± 2.09 mm on the right. Dong et al 17 found the width of the lateral mass to be 15.52 ± 1.35 mm on the left and 15.43 ± 1.06 mm on the right. Dong et al also found the lateral mass height to be 14.18 ± 1.88 mm on the left and 14.00 ± 2.03 mm on the right.…”
Section: Discussionmentioning
confidence: 98%
“…The height of the lateral mass was found to be 19.60 ± 2.24 mm on the left and 19.56 ± 2.09 mm on the right. Dong et al 17 found the width of the lateral mass to be 15.52 ± 1.35 mm on the left and 15.43 ± 1.06 mm on the right. Dong et al also found the lateral mass height to be 14.18 ± 1.88 mm on the left and 14.00 ± 2.03 mm on the right.…”
Section: Discussionmentioning
confidence: 98%
“…Os métodos de fixação variam desde amarrilha, fixação com parafuso transarticular, uso de ganchos, inserção de parafusos na massa articular ou translaminar no atlas 2,3,5,6,10,[12][13][14][15]18,20,22 . A lesão iatrogênica da artéria vertebral e a inserção de parafusos no canal medular são as complicações transoperatórias mais citadas 15,18 .…”
Section: Discussionunclassified
“…Com o desenvolvimento do diagnóstico e a precisão das técnicas cirúrgicas de fusão da articulação atlantoaxial, existem diversos estudos biomecânicos e clínico-cirúrgicos dessa região, enfatizando principalmente a estabilidade conseguida por diferentes técnicas de instrumentação 2,5,6,10,12,14,15,18,20,22 . Entretanto, existem poucos relatos na literatura enfatizando aspectos dimensionais, importância morfofuncional e cirúrgica do atlas.…”
Section: Introductionunclassified
“…The head was designed to match human sagittal inertia, mass, CoG location, size, and shape parameters (Hubbard and McLeod 1974;Walker et al 1973). The neck's geometry was designed to match the average sagittal centers of rotation (COR) for each vertebra (Amevo et al 1991;Dvorak et al 1991), sagittal vertebral body size (Dong et al 2003;Kandziora et al 2001;Wilke et al 1997), axial displacement (Pintar et al 1995), sagittal bending range of motion (ROM; Miura et al 2002) and the ratio of flexion to extension bending stiffness at each intervertebral level (Camacho et al 1997). A comparison to human mass properties for the head and neck is presented in Tables I and II.…”
Section: Modelmentioning
confidence: 99%
“…The intervertebral COR for a functional spinal unit determined by Dvorak and Panjabi (1991) were reported relative to coordinate systems located at the inferior and posterior margin of the inferior cervical vertebral body. In the as-built model of the surrogate spine, the vertebral body heights (H vb ) were anatomical (Dong et al 2003;Kandziora et al 2001;Wilke et al 1997). The depths (D vb ) were determined as follows: D vb for C7 was set arbitrarily but then the relative size between adjacent superior vertebral bodies (i.e., adjacent D vb ) along the cervical spine were preserved according to the mean vertebral body depth data of Kandziora et al (2001).…”
Section: Figurementioning
confidence: 99%